Development Simulation Model of Carbon Nanomaterial Quantum (CQN) System: Fluorescence Carbon Nanomaterials (FCN) - Anuar, Nur Anisah; Abd Razak, Nurulwafaa; Nordin, Norbaizura (Multidisciplinary Applied Research and Innovation, 2023)
The use of fluorescence carbon nanomaterials (FCN) quantum yield in the simulation model by using MATLAB was highlighted since the simulation data generated with software is it more accurate and precise than experimenting. The project conducted to determine carbon quantum dot (CQD) and FCN data, develop the coding graph of FCN in fluorescence emission system and simulate the the combination graph of FCN by using MATLAB with FCN red, FCN yellow, FCN green and FCN blue. The development required a coding and MATLAB software to generate figure of each and combination graph of FCN’s emission versus absorbance. The data shown the emission increase from FCN red (3.7848 × 1020 nm), to FCN yellow (6.0438 × 1020 nm), to FCN green (6.2981 × 1020 nm), and lastly FCN blue (1.1878 × 1021 nm). We can conclude that FCN blue and FCN green easier to yield. The quantum yield and size of particles also plays an important role to the emission rate of each FCN color. MATLAB proved that the graph generated was easy and smooth.